2012
DOI: 10.1111/j.1540-8159.2012.03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation Utilizing Remote Magnetic Navigation: A Review of Applications and Outcomes

Abstract: The utilization of the NIOBE™ magnetic navigation system (MNS, Stereotaxis, St. Louis, MO, USA) has increased significantly since the first published report in 2002. There has been much enthusiasm for this technology as a means to reduce radiation exposure to the patient and physician alike, and potentially decrease risks associated with catheter manipulation by less experienced operators. However, there are limited data regarding the acute, intermediate, and long-term results and procedural characteristics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 41 publications
3
75
0
1
Order By: Relevance
“…3 The main advantages of RMN-guided catheter ablation are precision, flexible navigation, reduced fluoroscopy time, and an excellent safety profile. 4 RMN-guided AF ablation procedures seem to be associated with fewer peri-procedural complications when compared to manually guided procedures. 5 However, previous studies regarding RMN-guided AF ablation have been limited in terms of sample size.…”
Section: Introductionmentioning
confidence: 91%
“…3 The main advantages of RMN-guided catheter ablation are precision, flexible navigation, reduced fluoroscopy time, and an excellent safety profile. 4 RMN-guided AF ablation procedures seem to be associated with fewer peri-procedural complications when compared to manually guided procedures. 5 However, previous studies regarding RMN-guided AF ablation have been limited in terms of sample size.…”
Section: Introductionmentioning
confidence: 91%
“…[26][27][28][29][32][33][34][35][36][37][38][39][40][41] It also has safety advantages with a lower risk of cardiac perforation due to the compliant nature of catheter and lower fluoroscopy exposure. Moreover, in patients with distorted anatomy or extensively dilated cardiac chamber, due to the magnetic ablation catheter being steered via the distal tip, it facilitates reaching all areas, thereby increasing sequential 3D 46 Wu et al 47 Wu et al 48 Akca et al 17 Ernst et al 15 Ueda et al †16 Horduna et al 49 Roy et al 50 Number of patients Wu et al 47 Wu et al 48 Akca et al 17 Ernst et al 15 Ueda et al †16 Horduna et al 49 Roy et al 50 7 ablation with RMT catheter (3 with 4 mm and 4 with 8 mm)…”
Section: General Experience With the Mns And Its Potential Advantagesmentioning
confidence: 99%
“…There are only case reports on successful AF ablation following ASD closure, 16,38 but studies on AF ablation using RMN in patients with structurally normal heart reported acceptable outcomes. 32,39 However, the retrograde approach is limited to the magnetic catheter without the ability to use a second diagnostic catheter (e.g., a circumferential mapping catheter) within the pulmonary veins.…”
Section: Asd Repair/ Percutaneous Asd Closure Devicementioning
confidence: 99%
“…14 Potential advantages of these technologies include increased safety, more precise catheter manipulation and increased stability. 15 A number of studies have demonstrated that the results of PV isolation with remote navigation are comparable with conventional ablation techniques. 16,17 However, they are also associated with drawbacks, the most important of which relate to the cost and logistical aspects of installation of the technology.…”
Section: Remote Navigation Technologies For Af Ablationmentioning
confidence: 99%